Associations of Dietary Intake and Sociodemographic Factors with the Incidence of T2DM among Obese Adults - Ghina Widiasih; Dono Indarto; Tri Nugraha Susilawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Type 2 diabetes mellitus (T2DM) is a major public health concern, particularly among obese individuals. Dietary intake, including energy, protein, and fiber consumption plays a key role in metabolic health, with sociodemographic factors influencing its mechanisms. Objective: This study aimed to analyze the associations of these dietary factors and T2DM incidence in obese adults in Surakarta city. This cross-sectional study included 100 obese adults from Surakarta. T2DM status was determined based on their medical records. Dietary intake data were collected using Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Sociodemographic data were collected by interview. Multiple binary logistic regression was performed to analyze the association between dietary intake and T2DM with p<0.05. The most participants were female (75.0%) and Javanese (82.0%). Daily fiber intake was significantly associated with a lower risk of T2DM (OR=0.04, 95%CI=0.01–0.14, p<0.001), while ethnicity, educational history, occupation, and monthly personal expenses were identified as significant risk factors (p<0.05). Further analysis, only daily fiber intake (aOR=0.06, 95%CI=0.01–0.29, p<0.001) and occupation (aOR=16.81, 95%CI=3.98–71.08, p<0.001) remained significantly associated with T2DM. Adequate daily fiber intake was the strongest protective factor, while individuals engaged in work were the strongest predictor of T2DM among obese adults in Surakarta city.